2019
DOI: 10.1051/0004-6361/201936273
|View full text |Cite
|
Sign up to set email alerts
|

The coronal temperature of NGC 4388 and NGC 2110 measured with INTEGRAL

Abstract: Aims. We aim to measure the physical properties of the hot X-ray corona of two active galactic nuclei, NGC 4388 and NGC 2110. Methods. We analysed the hard X-ray (20-300 keV) INTEGRAL spectrum in conjunction with archival XMM-Newton and NuSTAR data.Results. The X-ray spectrum of both sources is phenomenologically well described by an absorbed cut-off power law. In agreement with previous results, we find no evidence of a Compton reflection component in these sources. We obtain a high-energy cut-off of 200 +75 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 83 publications
6
5
0
Order By: Relevance
“…This research has made use of the NuSTAR Data Analysis Software (2017) is not strongly inconsistent with our analysis, we confirm that our lower NuSTAR-based constraint is robust despite achieving no improvement in terms of χ 2 reduction with respect to modeling presented in PaperI. Using INTEGRAL data and two epochs of NuSTAR data in the hard X-ray band, Ursini et al (2019) affirm our result, surpassing an earlier lower limit (>210 keV) found by Marinucci et al (2015).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…This research has made use of the NuSTAR Data Analysis Software (2017) is not strongly inconsistent with our analysis, we confirm that our lower NuSTAR-based constraint is robust despite achieving no improvement in terms of χ 2 reduction with respect to modeling presented in PaperI. Using INTEGRAL data and two epochs of NuSTAR data in the hard X-ray band, Ursini et al (2019) affirm our result, surpassing an earlier lower limit (>210 keV) found by Marinucci et al (2015).…”
supporting
confidence: 85%
“…NGC 4388.-For this target our constraint agrees very well with a more detailed study by Ursini et al (2019), including NuSTAR and INTEGRAL hard X-ray data. We also confirm E cut ≈ 200 keV from a dedicated multiepoch study with a different spectral model (M. Baloković et al 2020, in preparation).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…We used the results of Petrucci et al (2018), who fitted the XMM-Newton/pn data with nthcomp, also assuming a coronal temperature of 100 keV. The optical depths computed by the code are in the range 0.5-2, consistent with values commonly measured applying Comptonization models in spherical geometry (Tortosa et al 2018; see also Ursini et al 2019).…”
Section: Input Physical Parameterssupporting
confidence: 52%
“…The ionization parameter log ξ/ erg cm s −1 = 0.1 +0.1 −0.1 , and covering fraction found in our work, 0.21 +0.01 −0.01 , is consistent with Lubiński et al (2016). Current measurements of cutoff energies of the primary power-law component, range between 50 and 300 keV (Tortosa et al 2018;Molina et al 2019;Ursini et al 2019) for bright Seyfert 1 galaxies and require spectra extending well above 50 keV for better constraints. Using relativistic reflection model, we found a lower limit to the cutoff energy, Ec > 276 keV.…”
Section: Resultssupporting
confidence: 87%